Antibacterial properties of clinacanthus nutans extracts against porphyromonas gingivalis and aggregatibacter actinomycetemcomitans: An in-vitro study - Rohazila Mohamad Hanafiah; Wan Nur Alwani Wan Abdul Aziz; Khairine Alia Che Kamaruddin; Nurul Amira Ahmad Saikin; Muhammad Fahmi Yakop; Vuanghao Lim; Siti Aisyah Abd Ghafar; Nuramirah Azizan; Shahida Mohd Said (University of Dicle, 2024)
Indexed by Scopus